Effects of hypoventilation breathing on physical working capacity and functional status of skilled athletes during submaximal exercise - Fudin, N. A.; Klassina, S. Ya.; Pigareva, S. N.; Vagin, Y. E. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to analyze the effects of voluntary hypoventilation breathing on physical working capacity and functional status of qualified athletes during exercise to muscular failure. The study involved 25 young males with different physical fitness levels. All of them were examined twice, and in both cases they were asked to perform a step load test to muscular failure on a cycle ergometer. Moreover, the first testing was carried out before the hypoventilation breathing training, the second one - after it. The subjects` condition was evaluated at rest and during the stress test. We registered the ECG and pneumogram, heart rate and respiration rate, time of exercise to muscular failure and its "physiological penalty", external respiration rates and level of blood oxygen saturation. Before and after the testing, blood pressure and timed inspiratory capacity were measured. The hemodynamic parameters were estimated by means of a calculation. It was shown that hypoventilation training develops increased hypoxic tolerance and physical working capacity in athletes against the background of "economization" of their respiratory function and stability of blood oxygenation.